(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current study is a content analysis of research in Physics education published between 2008 and 2013, which was obtained from the Turkish national academic network and information center (ULAKBIM) and EBCSO. Its goal is to guide researchers who plan to undertake studies in this field by describing the tendencies of 105 papers on physics education in terms of their methodology, subject areas, research titles, data analysis strategies, and sampling kinds. The study’s data is presented in visual, frequency, and percentage tables. According to the findings, the majority of physics education research was conducted in 2013. When physics is used as a subject title, it is discovered that a large portion of the studies are about mechanical physics and electric physics; however, when they are analyzed from the perspective of their research titles, it appears that teaching methods and cognitive dimensions have gained prominence. The study’s findings show that the majority of physics education studies are quantitative in design; achievement tests, interest tests, attitude tests, and aptitude tests are primarily employed as data collection tools; and a descriptive analysis method is used for data analysis. Furthermore, the researchers decided to select their sample group from secondary school pupils, with sample sizes ranging from 31 to 100 individuals. In this study, the researchers of physics education are given the essential advice.